MEKANISME TATA KELOLA PERUSAHAAN DAN MANAJEMEN LABA DALAM MENJELASKAN PENGARUH ECONOMIC VALUE ADDED TERHADAP PENCIPTAAN NILAI BAGI PEMEGANG SAHAM - , Kartika Sari Lubis ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to (a) determine the effect of Economic Value Added towards firms value, (b) determine the effect of Economic Value Added towards firms value at companies that have different corporate governance, c) determine the effect of Economic Value Added on firms value that have different levels of earning management, and (d) determine the effect of corporate governance on earning management. This study uses secondary quantitative data such as: financial statement data of manufacturing companies listed on the Indonesia Stock Exchange which includes information of commissioners and independent commissioners